Microhabitat complexity influences fear acquisition in fathead minnows. (6th November 2019) - Crane, Adam L; Ferrari, Maud C O; Rivera-Hernández, Ita A E; Brown, Grant E
Abstract: Habitat varies in structure, with animals often preferring a certain degree of microhabitat complexity that facilitates fitness-related activities such as predator avoidance. Environments with high predation risk can induce elevated baseline fear and neophobia in prey, but whether microhabitat complexity influences the acquisition of neophobia has yet to be reported. Here, we tested whether exposure to predation risk induces different levels of fear in microhabitats that differed in complexity. We exposed fathead minnows, Pimephales promelas, to predation risk repeatedly (12 times over 4 days) in the form of damage-released chemical alarm cues (compared to water control) in tanks with vertical plant structure distributed either throughout the tank (complex habitat) or clumped together (simple habitat). Then, we tested minnows before and after exposure to a novel odor in tanks with either the same microhabitat complexity (i.e., familiar habitats) or in tanks with novel habitat that had different substrate structure and no vertical structure. Minnows in the complex habitat showed less overall movement one day after the background risk period, whereas individuals in the simple habitat showed reduced movement regardless of prior risk exposure. We observed stronger effects in the novel habitat, where background risk in both simple and complex habitats caused neophobia. However, individuals from the simple background habitat showed higher baseline fear behaviors. Hence, for minnows, low microhabitat complexity appears to lead to elevated fear, which remains even after a habitat change. Lay Summary: High-risk environments can induce a state of elevated baseline fear and neophobia in prey, but how microhabitat complexity influences the acquisition of neophobia has yet to be reported. We observed the behavior of minnows after manipulating vertical plant structure (simple or complex) and exposure to predation risk (present or absent) in the form of damage-released conspecific chemical cues. Low microhabitat complexity led to increased predation fear, which intensified upon moving to novel habitats.